On the Necessity of Using Average Cost as a Base for Transfer Price - Tomáš Buus; Jaroslav Brada (European Financial and Accounting Journal, 2008)
Both older and recent literature on transfer pricing is not unified about the opinion whether optimal transfer price should be equal to marginal cost of supplying company and set by centralized decision (of vertically integrated multibusiness enterprise headquarters) or whether it should be set by negotiation or even set on level of market (arms-length) price. Those, who argue for setting transfer price by negotiation or at the market price base their arguments on market imperfections like information asymmetry, motivation of managers, et cetera. This paper deals inter alia with problem of methodology transfer pricing mathematical modelling. We prove that optimal transfer price should be equal to average cost of the supplying division plus part (or whole) economic profit of the multibusiness enterprise, independent on the market conditions at the market of either intermediate or final product. Setting transfer price on the level of marginal cost is inefficient and would earlier or later lead to loss of multibusiness enterprise's ability to compete its rivals. Applicability of results of our research on multinational enterprises gives us possibility to use it for further research on optimal design of transfer pricing rules setting and of multinationals' taxation.
Keywords: D21; D29; G39; 650; Multibusiness enterprise; OECD taxation guidelines; Transfer pricing; Vertical integration